2015
DOI: 10.1007/s00467-015-3181-8
|View full text |Cite
|
Sign up to set email alerts
|

How does your kidney smell? Emerging roles for olfactory receptors in renal function

Abstract: Olfactory receptors (ORs) are chemosensors that are responsible for one’s sense of smell. In addition to this specialized role in the nose, recent evidence suggests that ORs are also found in a variety of additional tissues including the kidney. As this list of renal ORs continues to expand, it is becoming clear that these ORs play important roles in renal and whole-body physiology, including a novel role in blood pressure regulation. In this review, we highlight important considerations that are crucial when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 86 publications
0
27
0
Order By: Relevance
“…However, we found that both S3 and BUMPT cells have low transfection efficiencies and are poor expressers of exogenously expressed flag-tagged Olfr1393. This is not at all uncommon; functional expression of exogenous ORs is quite difficult as they are often retained in the endoplasmic reticulum and degraded instead of being functionally expressed on the plasma membrane 8 25 . However, in screening additional renal epithelial cells lines we determined that polarized MDCK cells successfully traffic a subset of ORs, including Olfr1393.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that both S3 and BUMPT cells have low transfection efficiencies and are poor expressers of exogenously expressed flag-tagged Olfr1393. This is not at all uncommon; functional expression of exogenous ORs is quite difficult as they are often retained in the endoplasmic reticulum and degraded instead of being functionally expressed on the plasma membrane 8 25 . However, in screening additional renal epithelial cells lines we determined that polarized MDCK cells successfully traffic a subset of ORs, including Olfr1393.…”
Section: Resultsmentioning
confidence: 99%
“…Olfactory receptors (ORs) are seven transmembrane domain G protein-coupled receptors (GPCRs) that serve as the chemical sensors of smell in the olfactory epithelium (OE). While these receptors were originally thought to be restricted to the nose 1 , it is now appreciated that ORs and other sensory receptors are found in a variety of other tissues where they play important physiological functions 2 3 4 5 6 7 8 9 . We previously reported that at least 10 different ORs as well as their downstream signaling components (adenylate cyclase 3 and the olfactory G protein) are expressed in the kidney, and that one of these renal ORs contributes to blood pressure regulation 6 10 .…”
mentioning
confidence: 99%
“…Function of the sensory receptors is often dependent on the localization of the receptors, however, there are few antibodies available for these proteins, and the ones that do exist from commercially available sources are typically unreliable ( Shepard and Pluznick, 2015 ). Thus, to glean potential function from these receptors, we utilized RNAscope, a method that relies on unique probes to localize individual mRNA strands in a tissue section.…”
Section: Resultsmentioning
confidence: 99%
“…Olfactory receptors (ORs) are seven-transmembrane domain G protein-coupled receptors (GPCRs) that functions as chemosensors within the olfactory epithelium (OE) of the nose, where they detect the small molecules we perceive as odorants 1 . There are more than 1000 OR genes in mice and approximately 390 in humans, making them the largest receptor family in mammals 2 , 3 . The odor information detected by this multiplicity of ORs is processed through a common signaling pathway: when an OR binds to its odorant, it activates a single G protein species, the olfactory trimeric G protein (G olf ), which then activates the olfactory isoform of adenylate cyclase (Adcy3) 1 , 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The odor information detected by this multiplicity of ORs is processed through a common signaling pathway: when an OR binds to its odorant, it activates a single G protein species, the olfactory trimeric G protein (G olf ), which then activates the olfactory isoform of adenylate cyclase (Adcy3) 1 , 4 , 5 . Although these receptors were originally thought to be restricted to the nose 6 , it is now recognized that ORs are found in a variety of other tissues where they act as sensitive and selective chemoreceptors that influence many physiological processes 2 4 , 7 10 . Pluznick et al .…”
Section: Introductionmentioning
confidence: 99%